Humidification of incubators. Issue 3 (March 1985) - Harpin, V A; Rutter, N
Abstract : The effect of increasing the humidity in incubators was examined in 62 infants of less than 30 weeks' gestation. Thirty three infants nursed in high humidity for two weeks were compared retrospectively with 29 infants from an earlier study who were nursed under plastic bubble blankets or with topical paraffin but without raised humidity. Humidification reduced skin water loss and improved maintenance of body temperature from birth, but did not delay the normal postnatal maturation of the skin. Infants nursed without humidity frequently became hypothermic in spite of a high incubator air temperature. These advantages must be weighed against the finding that overheating was more common and Pseudomonas was more commonly isolated from the infants. It is recommended that incubator humidity is raised for babies under 30 weeks' gestation in the first days of life but meticulous attention should be paid to fluid balance, avoiding overheating, and cleansing of the humidifier reservoir.